2004
DOI: 10.1097/01.ccm.0000147685.79487.28
|View full text |Cite
|
Sign up to set email alerts
|

Cycling empirical antimicrobial agents to prevent emergence of antimicrobial-resistant Gram-negative bacteria among intensive care unit patients

Abstract: In this study, antimicrobial cycling did not result in a significant change in enteric acquisition of resistant Gram-negative bacteria among intensive care unit patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
68
1
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(71 citation statements)
references
References 23 publications
0
68
1
2
Order By: Relevance
“…This is probably achieved by decreasing multi-resistant nosocomial infections in patients outside the intervention unit, not participating in the cycling protocol. 18 Warren et al 10 failed to show any changes in P. aeruginosa and Gram-negative enterics resistance in the ICU setting, but the rest of the hospital had a decrease in susceptibility over the same period of time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is probably achieved by decreasing multi-resistant nosocomial infections in patients outside the intervention unit, not participating in the cycling protocol. 18 Warren et al 10 failed to show any changes in P. aeruginosa and Gram-negative enterics resistance in the ICU setting, but the rest of the hospital had a decrease in susceptibility over the same period of time.…”
Section: Discussionmentioning
confidence: 99%
“…While several studies have suggested that it can be effective in decreasing antibiotic resistance in a unit, other studies have shown no effect, and there are many unanswered questions. 4,[6][7][8][9][10][11] The first issue limiting such a program is the difficulty of implementing the protocol and guaranteeing compliance with the protocol. With the help of the pharmacy and proper education, it can be performed in the community or in the academic setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the hospital-wide level, two therapeutic approaches are typically employed: mixing therapy (i.e., two or more drugs are used simultaneously in the hospital, where each patient receives a single drug) and periodic hospital-wide rotation of antibiotics (i.e., two or more drugs can be alternated periodically within a hospital). While clinical trials for different bacterial infections produced mixed results (4,8,33,34,40), theoretical results typically suggest that a mixing strategy minimizes the evolution of MDR compared to that of hospital-wide rotation (9,11,42). The mixing strategy is believed to increase the rate at which bacteria are exposed to different antibiotics relative to rotation, therefore minimizing the opportunity for resistance evolution.…”
mentioning
confidence: 99%
“…A limited number of studies has shown a decreased incidence of antibioticresistant Gram-negative infections, particularly ventilatorassociated pneumonia (VAP), a decreased resistance pattern of Pseudomonas aeruginosa and lower infection-related mortality rates [19][20][21]24]. Other studies have not observed any advantage of this strategy [26]. To date, the synthesis of these results is that there is insufficient evidence to recommend antibiotic cycling as a standard measure to reduce antibiotic resistance [27,28].…”
Section: Introductionmentioning
confidence: 81%